2012
DOI: 10.1037/a0025971
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of activating thoughts of God on self-regulation.

Abstract: Despite the cultural ubiquity of ideas and images related to God, relatively little is known about the effects of exposure to God representations on behavior. Specific depictions of God differ across religions, but common to most is that God is (a) an omnipotent, controlling force and (b) an omniscient, all-knowing being. Given these 2 characteristic features, how might exposure to the concept of God influence behavior? Leveraging classic and recent theorizing on self-regulation and social cognition, we predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 116 publications
(174 reference statements)
6
106
1
5
Order By: Relevance
“…As Randolph-Seng and Nielsen (2008) themselves pointed out in a commentary on Shariff and Norenzayan (2007), a more parsimonious explanation is that any words sharing a stereotypical connection with prosociality lead to honest behavior due to the priming of general, commonly held cultural associations with morality (Laurin et al, 2011). For example, some have suggested that such priming activates evolved mechanisms that promote prosociality via the activation of third-party watchfulness or reputational concems (Norenzayan & Shariff, 2008).…”
Section: Mccullough and Willoughbymentioning
confidence: 95%
“…As Randolph-Seng and Nielsen (2008) themselves pointed out in a commentary on Shariff and Norenzayan (2007), a more parsimonious explanation is that any words sharing a stereotypical connection with prosociality lead to honest behavior due to the priming of general, commonly held cultural associations with morality (Laurin et al, 2011). For example, some have suggested that such priming activates evolved mechanisms that promote prosociality via the activation of third-party watchfulness or reputational concems (Norenzayan & Shariff, 2008).…”
Section: Mccullough and Willoughbymentioning
confidence: 95%
“…Second, outside performance contexts, religious concepts, which are closely linked to ritual practice and prayer, have been shown to improve self-regulation and self-control (e.g., Fishbach, Friedman, & Kruglanski, 2003;Laurin, Kay, & Fitzsimons, 2012;Mazar, Amir, & Ariely, 2008;Rounding, Lee, Jacobson, & Ji, 2012;Sharif & Norenzayan, 2007;Xygalatas, 2013; but see Good, Inzlicht, & Larson, 2015), suggesting that the rituals common to many religions are associated with the ongoing goals of impulse control and self-monitoring (Koole, et al, 2010;McCullough & Willoughby, 2009;Norenzayan, Shariff, Gervais, Willard, McNamara, Slingerland, & Henrich, 2016;Rossano, 2012). The regular practice of effortful religious rituals signals personal commitment and builds implicit self-control over time, promoting adaptive behaviors that enhance health and well-being (Whitehouse, 2002;Wood, 2016).…”
Section: Psychology Of Rituals 21mentioning
confidence: 99%
“…The conventional understanding is that reminders of God activate public self-awareness, which is associated with impression management concerns (Bögels, Alberts, & de Jong, 1996;Saboonchi, Lundh, & Ö st, 1999). Furthermore, this explanation does not fit well with Carter, McCullough, and Carver (2012) work, which found that self-monitoring, similar to public self-awareness, mediates the relationship between religion and selfcontrol processes that foster moral and socially acceptable behavior (e.g., Baumeister & Exline, 1999;DeWall et al, 2014;Laurin, Kay, & Fitzsimons, 2012;McCullough & Willoughby, 2009). Up to this point, the most direct evidence for the public-selfawareness explanation was provided by Gervais and Norenzayan (2012), but this study found a clear pattern that priming God increased private-but not public-self-awareness.…”
Section: Discussionmentioning
confidence: 85%
“…Instead, in the context of this larger literature, this study underscores the importance of understanding the effect that priming God has on selfawareness more clearly. It has implications for moral behavior (Shariff & Norenzayan, 2007), self-regulation (DeWall et al, 2014;Laurin et al, 2012), and the self-concept (Hill & Hall, 2002). Furthermore, it raises an intriguing question about why priming God would have an effect on private self-awareness for believers and unbelievers alike.…”
Section: Discussionmentioning
confidence: 99%